Effect of urea as a chaotropic agent on self-association of organic molecules in aqueous flow batteries - Shahsavan, Mahsa; Wiberg, Cedrik; Poskela, Aapo; Martinez-Gonzalez, Eduardo; Peljo, Pekka (Royal Society of Chemistry, 2026)
This paper investigates the effect of urea, a widely used denaturing co-solute, on the aggregation of promising candidates for aqueous organic flow batteries, specifically 9,10-anthraquinone-2,7-disulfonic acid (AQDS) and naphthalene diimide derivatives (NDIs). These molecules undergo aggregation through π-π interactions of their aromatic cores. We evaluated how urea influences molecular interactions and electrochemical behavior of these molecules by nuclear magnetic resonance (NMR), cyclic voltammetry (CV), rotating disk electrode (RDE), and flow battery testing. While NMR confirmed that urea effectively disrupts π-π stacking and reduces the concentration-dependent shifts and peak broadening, electrochemical measurements showed that this effect is only partial. These results highlight the difference between molecular-level disruption of aggregation and limited improvements in electrochemical performance.